The Pengaruh Pelatihan terhadap Kinerja Karyawan Housekeeping di Sheraton Bali Kuta Resort - Pradipta Adisastra, Nyoman Gandha; Diwyarthi, Ni Desak Made Santi; Sri Sadjuni, Ni Luh Gde (Journal of Hotel Management, 2025)
This research aims to analyze the effect of training on employee performance in the Housekeeping Department at Sheraton Bali Kuta Resort. Through quantitative methods, this study uses simple linear regression analysis to test the effect of training variables on employee performance. Data was collected through questionnaires distributed to Housekeeping employees and analyzed using SPSS 16.0 software. The results showed that there is a significant influence between training and employee performance. This is indicated by the results of the t test, where the calculated t value of 4.992 is greater than the t table of 2.045, which indicates a real relationship between the two variables. In addition, the results of the determination analysis show that training contributes 46.2% to improving employee performance, while the remaining 53.8% is influenced by other variables not mentioned in this study. The conclusion of this study is that training has a significant influence on the performance of Housekeeping employees at Sheraton Bali Kuta Resort, but there are other variables that also play an important role in influencing employee performance. Therefore, hotel management is advised not only to focus on training, but also to pay attention to other factors that can improve overall employee performance.